Fan studies in Brazil: the internet-centric bias and its impact on understanding local fandoms. - Amado, Aianne; Vieira, Eloy (AoIR Selected Papers of Internet Research, 2026)
Fan Studies as an academic field has been significantly shaped by american researchers like Henry Jenkins (1992, 2006a, 2006b), who conceptualized fans as active participants who engage with media texts through creative production. Since its beginning, the internet has become central to Fan Studies, marking what Gray, Sandvoss, and Harrington (2007) call the “second wave” of research, with a focus on social media and digital fan practices.In Brazil, Fan Studies emerged in 2002 and aligned with the international references. Morover, Cyberculture scholars were among the few willing to support and metor such studies. Due to this historical context, Brazilian research on fandoms has largely prioritized internet-based interactions, reflecting a bias that overlooks offline fan practices. This focus is evident in literature reviews (Carlos, 2015; Amado, 2020) that highlight digital culture as a dominant theme.While the internet is crucial for contemporary fandoms, this emphasis may marginalize underrepresented fan groups. Internet access in Brazil expanded from 8% in 2002 to nearly 85% in 2024 (Laboissière, 2024), yet disparities in broadband quality and digital literacy persist (Knop, 2020). Consequently, digital Fan Studies risk favoring privileged demographics while neglecting fans from rural areas, lower-income communities, and older age groups.Scholars like Costa (2018) argue for a national theoretical framework to address these gaps. This article calls for a broader, more inclusive approach to Brazilian Fan Studies, recognizing the impact of internet-centrism and advocating for methodologies that reflect the country’s diverse fan cultures.